2016
DOI: 10.1080/10410236.2016.1214216
|View full text |Cite
|
Sign up to set email alerts
|

Parental Perception of Self-Empowerment in Pediatric Pharmacogenetic Testing: The Reactions of Parents to the Communication of Actual and Hypothetical CYP2D6 Test Results

Abstract: Concerns about the ethical and social implications of genetics persist as more applications of genetic and genomic technology have become available. Pediatric testing for genetic influences on response to opioids like codeine is one area of application. We interviewed parents of children enrolled in a mixed-methods study following the communication of actual or hypothetical results for CYP2D6, which impacts opioid response. Forty-one parents of children naïve to opioids and 42 parents of children previously ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In contrast, one study noted that parents who feel expected to cope without being given adequate coping skills may be disempowered [25]. Finally, developing an identity as an advocate appeared to promote empowerment [35,45,38].…”
Section: Building Personal Capacity and Narrative-mentioning
confidence: 96%
See 4 more Smart Citations
“…In contrast, one study noted that parents who feel expected to cope without being given adequate coping skills may be disempowered [25]. Finally, developing an identity as an advocate appeared to promote empowerment [35,45,38].…”
Section: Building Personal Capacity and Narrative-mentioning
confidence: 96%
“…Empowering Others-Finally, empowered parents may work to empower others [25,37,38]. Specifically, one study reported empowered mothers sharing their experiences in hopes of empowering other mothers in similar situations [39].…”
Section: 26mentioning
confidence: 99%
See 3 more Smart Citations